Spacer Length Dependence on the Efficiency of Dimeric Anionic Peptides in Gene Transfer by Glycosylated Polylysine/Plasmid Complexes. Issue 5 (October 2000) - Freulon, I.; Monsigny, M.; Midoux, P.; Mayer, R.
Abstract : Amphiphilic anionic peptides have been used to enhance the efficiency of transfection by helping plasmids to escape from endosomes to the cytosol. It has been shown that efficiency of an eicosamers containing five glutamyl residues (E5), can be considerably enhanced either by transforming it into a dimer or by adding a tripeptide WYG in a C-terminal position (E5WYG). The dimerization of the peptide E5WYG leads to a more efficient tool when the dimerization device includes the tripeptide WYG unit and a longer spacer arm made of Gly-γAla-γAla residues, but to a 10-fold less efficient tool when the dimerization device includes a shorter spacer, a glycyl residue. Both dimers are taken up by the cells to a similar extent. Both dimers seem to be surrounded similarly as far as the environmental pH is concerned. In contrast, we found a correlation between the propensity of the peptides to adopt a helical structure at neutral pH and the gene transfer efficiency.